KEANEKARAGAMAN JENIS MAKROFUNGI DI HUTAN TAHURA IR. HERMAN YOHANES DESA KOTABES KECAMATAN AMARASI KABUPATEN KUPANG - Nosintha Huru; Mario J. Santrum; Maryanto C. Honin (SINERGI : Jurnal Riset Ilmiah, 2026)
This study, which examines the diversity of macrofungi in the Prof. Ir. Yohanes Forest Park, Kotabes Village, Amarasi District, Kupang Regency, aimed to determine the diversity of macrofungi in the Prof. Ir. Yohanes Forest Park, Kotabes Village, Amarasi District, Kupang Regency. This study was conducted in the Prof. Ir. Yohanes Forest Park, Kotabes Village, Amarasi District, Kupang Regency, in September 2025. The method used in this study was the line transect and plot method, using 10 observation transects, each with 8 plots. Based on the results of the study, 10 species of macrofungi were identified in the Prof. Ir. Yohanes Forest Park: Trametes versicolor, Ganoderma lucidium, Lentinus connatus, Hydnochaeta olivacea, Coltricia perennis, Trametes elegans, Ganoderma sp., Pleurotus ostreatus, Lepiota cristata, and Ganoderma applanatum. The macrofungal diversity index (H') in the Prof. Ir. Yohanes Forest Park is 1.49, categorized as moderate.